Letter (copy) - Wild, Sam
1952 035-0027-004 COPY INTERNATIONAL BRIGADE ASSOCIATION AND FRIENDS OF REPUBLICAN SPAIN 374, Gray's Inn Road, London, W.C.1. Phone TERminus 3478 Dear Sir & Brother, Last July, the nation-wide protest movement on behalf of Gregorio Lopez Raimundo and 26 other leaders of the Barcelona general strike, who were being court-martialed by the Franco authorities, culminated in the sending by our Association of Mr. David Widdicombe, Ll.B., a member of the Society of Labour Lawyers, together with an interpreter, to attend the trial as an observer. Similar observers were sent from Italy, Belgium and France. As a result of this the world protest movement succeeded in saving their lives and securing the release of 23 of the prisoners. Lopez Raimundo, however, General Secretary of the United Socialist Party of Catalonia together with three others, is still imprisoned. The campaign for their immediate release is being maintained by our Association. As was emphasised in the General Council's Report to the Margate Trades Union Congress there has been an alarming increase this year in the persecution of anti-Franco trade unionists and democrats in Spain. Three mass trials have been held. Some of the accused had been in prison for nearly two years without trial; others have been the victims of brutality and torture. The death penalty has been demanded in a number of cases and five have been executed. At the moment of writing, we have just received word that a further mass trial is pending of 42 young Spanish democrats, many of whom are members of the United Socialist Youth of Catalonia and who have been held in prison since December, 1949. At this year's Annual Conference of the Labour Party, both by resolution and in speeches, the Franco regime was condemned. We appeal to you to help us translate this condemnation into active assistance for our brother trade unionists and democrats who are struggling to regain their liberties:— 1. By sending a donation to help the International Brigade Association and Friends of Republican Spain continue the work it is doing for Franco's prisoners and for Spain. 292/946/35/28(ii)